ETHNOMATHEMATICS COMIC MEDIA IN PRIMARY MATHEMATICS LEARNING: A REVIEW OF RESEARCH TRENDS (2019–2025) - Suci Indiri; Decky Avrillianda; Ellianawati Ellianawati (Jurnal Cakrawala Pendas, 2025)
Mathematics education in primary schools often faces challenges, such as low student engagement and difficulty in understanding abstract concepts. Ethnomathematics comics are a contextual and engaging learning medium, believed to address these issues by providing visualisations and narratives connected to students' local culture. The objective of this study is to identify and analyse research trends on ethnomathematics comic media in primary school mathematics education from 2019 to 2025 using the Systematic Literature Review (SLR) method. This objective is important to understand the direction of existing studies, identify gaps in the literature, and provide a foundation for further research and the development of media that is more relevant to contextual learning needs. Analysis was conducted using Publish or Perish (PoP) and VOSviewer, resulting in 9 journal articles and 2 conference proceedings indexed in Google Scholar and Scopus from the period 2019–2025. The research findings indicate that (1) the trend of ethnomathematics comic research continues to develop and remains relevant in the context of primary education; (2) the dominant cultural elements integrated into the comics are local cultures familiar to students and adapted to the unique characteristics of each region; and (3) the use of ethnomathematics comics has proven effective in enhancing students' conceptual understanding and learning engagement in primary schools. These findings suggest the potential for developing more contextually relevant, culture-based educational media. Additionally, they provide new directions for research and practice in primary education.